Five energy metabolism pathways show distinct regional distributions and lifespan trajectories in the human brain - Pourmajidian, Moohebat; Hansen, Justine Y.; Shafiei, Golia; Misic, Bratislav; Dagher, Alain (PLOS Biology, 2026)
Energy metabolism involves a series of biochemical reactions that generate ATP, utilizing substrates such as glucose and oxygen supplied via cerebral blood flow. Energy substrates are metabolized in multiple interrelated pathways that are cell- and organelle-specific. These pathways not only generate energy but are also fundamental to the production of essential biomolecules required for neuronal function and survival. How these complex biochemical processes are spatially distributed across the cortex is integral to understanding the structure and function of the brain. Here, using curated gene sets and whole-brain transcriptomics, we generate maps of five fundamental energy metabolic pathways: glycolysis, pentose phosphate pathway, tricarboxylic acid cycle, oxidative phosphorylation and lactate metabolism. We find consistent divergence between primarily energy-producing and anabolic pathways, particularly in unimodal sensory cortices. We then explore the spatial alignment of these maps with multi-scale structural and functional attributes, including metabolic uptake, neurophysiological oscillations, cell type composition, laminar organization and macro-scale connectivity. We find that energy pathways exhibit unique relationships with the cellular and laminar organization of the cortex, pointing to the higher energy demands of large pyramidal cells and efferent projections. Finally, we show that metabolic pathways exhibit distinct developmental trajectories from the fetal stage to adulthood. The primary energy-producing pathways peak in childhood, while the anabolic pentose phosphate pathway shows greater prenatal expression and declines throughout life. Together, these results highlight the rich biochemical complexity of energy metabolism organization in the brain.